USE OF MOXIBUSTION AND ACUPUNCTURE IN PREGNANT WOMEN WITH BREECH PRESENTATION: AN INTEGRATIVE REVIEW - Mariana Haddad Rodrigues; Vivian Inácio Zorzim (Universidade Federal do Paraná, 2017)
The objective in this study was to develop an integrative review to identify publications on moxibustion and acupuncture to turn fetuses in breech position. The research tool Patient, Intervention, Comparison and Outcome, available through the database of the United States National Library of Medicine, was used to produce a list of articles. The words used for the search were: breech, moxibustion, acupuncture and cephalic. The search was undertaken in March 2016. Twenty-four registers were found, 18 of which were analyzed, seven of them favorable to the use of moxibustion and five unfavorable. Based on the studies developed on the theme, there is evidence that moxibustion is safe and effective to try and "correct" breech presentations, as a tool to complement the care midwifery professionals provide.